Comparison of dynamic features of pelvic floor muscle contraction between men with and without incontinence after prostatectomy and men with no history of prostate cancer. Issue 1 (13th November 2019) - Stafford, Ryan E.; Coughlin, Geoff; Hodges, Paul W.
Abstract: Aim: To compare features of pelvic floor muscle function between men with and without incontinence after prostatectomy and men with no history of prostate cancer. Methods: The study included men with incontinence postprostatectomy (PPI; n  = 20), continent men postprostatectomy (PPC; n  = 23) and a control group (CC; n  = 20). Transperineal ultrasound imaging recorded motion associated with contraction of the striated urethral sphincter (SUS), puborectalis (PR) and bulbocavernosus (BC) muscles during maximal voluntary contraction (MVC), submaximal efforts, evoked coughing and bearing down. Anatomical landmark displacements were compared between groups and receiver operating characteristics were calculated to determine the threshold displacements that best differentiated PPI and PPC. Results: PPC demonstrated greater SUS, PR, and BC displacement than PPI during MVC (All: P  < .01). During cough, PPC had less bladder neck descent (PR lengthening), and greater BC shortening ( P  = .003) than both PPI and CC. PPC also achieved greater SUS displacement ( P  = .025) than PPI during cough. The best discrimination between PPI and PPC was achieved when men exceeded threshold displacement for both SUS (≥4.1 mm) and PR (≥2.4 mm) during MVC. The urethral length was not different between PPC and PPI. Conclusions: Men who were continent postprostatectomy achieved greater shortening of the SUS, PR, and BC muscles than incontinent men during voluntary contractions and demonstrated better PR and BC function than control participants during coughing. The capacity to shorten the SUS ≥4.1 mm and the PR ≥2.4 mm best distinguished between PPI and PPC and might be a useful clinical target for conservative treatment programs.